A role of the sodium pump in spreading ischemia in rats. Issue 5 (May 2017) - Major, Sebastian; Petzold, Gabor C; Reiffurth, Clemens; Windmüller, Olaf; Foddis, Marco; Lindauer, Ute; Kang, Eun-Jeung; Dreier, Jens P
In rats, spreading depolarization induces vasodilation/hyperemia in naïve tissue but the inverse response when artificial cerebrospinal fluid is topically applied to the brain containing (a) a nitric oxide–lowering agent and (b) elevated K + . The inverse response is characterized by severe vasoconstriction/ischemia. The perfusion deficit runs together with the depolarization in the tissue (=spreading ischemia). Here, we found in male Wistar rats that pre-treatment with artificial cerebrospinal fluid containing elevated K + in vivo led to a selective decline in α2 /α3 Na + /K + -ATPase activity, determined spectrophotometrically ex vivo. Moreover, spreading ischemia, recorded with laser-Doppler flowmetry and electrocorticography, resulted from artificial cerebrospinal fluid containing a nitric oxide–lowering agent in combination with the Na + /K + -ATPase inhibitor ouabain at a concentration selectively inhibiting α2 /α3 activity. Decline in α2 /α3 activity results in increased Ca 2+ uptake by internal stores of astrocytes, vascular myocytes, and pericytes since Ca 2+ outflux via plasmalemmal Na + /Ca 2+ -exchanger declines. Augmented Ca 2+ mobilization from internal stores during spreading depolarization might enhance vasoconstriction, thus, contributing to spreading ischemia. Accordingly, spreading ischemia was significantly shortened when intracellular Ca 2+ stores were emptied by pre-treatment with thapsigargin, an inhibitor of the sarco(endo)plasmic reticulum Ca 2+ -ATPase (SERCA). These findings might have relevance for clinical conditions, in which spreading ischemia occurs such as delayed cerebral ischemia after subarachnoid hemorrhage.